Antimicrobial evaluation of hibiscus rosa sinensis plant extract against escherichia coli / Dhiya Adilia Roslan - Roslan, Dhiya Adilia (Faculty of Applied Sciences, 2016)
Medicinal plant play many significant roles in treating various kind of disease and act as antimicrobial agent as it claimed to have antimicrobial compounds in various parts of plant. The objective of this research is to compare the antimicrobial activity from flower, stem and leaves of Hibiscus rosa sinensis and to evaluate antimicrobial activity of methanol extracts of hibiscus towards food-borne pathogen Escherichia coli and Escherichia coli 0157:H7. In this preliminary investigation, the crude extract was prepared through maceration of dried flower, leaf and stems of the plant by methanolic solution. The antibacterial activity was screened by using Minimum Inhibitory Concentration (MIC) broth microdilution in and Minimum Bactericidal Concentration (MBC). The antibacterial activity were assessed by the turbidity of inoculum in MIC and the reduce of 99.9% or more growth of bacteria on plate from the initial inoculum for MBC. All methanolic extract showed antibacterial activity towards both Escherichia coli and Escherichia coli 0157:H7. The leaf extract of plant showed the highest antimicrobial activity against Escherichia coli, and the stem extract as the highest antimicrobial activity on Escherichia coli O 157 :H7.